An empirical evaluation of the MATRICS Consensus Cognitive Battery in bipolar disorder. (9th October 2013) - Van, Tamsyn E; Rossell, Susan L
<x xml:space="preserve">Abstract</x> Objectives There is a large body of evidence to indicate that neurocognitive impairments in bipolar disorder (BD) may represent viable endophenotypes; however, a standard consensus‐based battery of cognitive tests used to measure them is yet to appear. There is potential for a neurocognitive battery which was developed for use in the related disorder, schizophrenia – the MATRICS Consensus Cognitive Battery (MCCB) – to provide a consistent measurement tool with a standard to which the cognitive capacity of BD can be compared to other disorders. However, its suitability for capturing neurocognitive impairment in BD cohorts is not well established. Moreover, neurocognitive tests recently recommended by the International Society for Bipolar Disorders (ISBD) for inclusion in a consensus neurocognitive battery for BD have not been evaluated in the context of the MCCB. An evaluation of (i) the clinical efficacy of the MCCB and (ii) the tests recommended by the ISBD in a BD cohort were the aims of the current study. Methods A total of 50 patients with BD (mean age = 38 years) and 52 healthy controls (mean age = 34 years) completed all of the MCCB subtests, in addition to the well‐recognized Trail Making Test–Part B and the Colour–Word Stroop. Results Multivariate analyses of variance of the MCCB domains revealed a significant group effect for overall cognition, and significantly reduced patient performance on speed of processing, working memory, and visual and verbal learning. A second multivariate analysis of variance using a newly created composite score called executive function, comprising scores on an existing MCCB subtest in addition to TMT‐B and Colour–Word Stroop, revealed significant differences on this domain as well. Subgroup analysis indicated that there were no differences in any domain score performance between symptomatic and euthymic patients, or bipolar I and II disorder patient groups. Conclusions Our findings suggest that the MCCB and two additionally recommended ISBD executive function measures form a promising consensus‐based research tool for examining neurocognition in BD.